Transcultural humanities in South Asia : critical essays on literature and culture - Anwar, Waseem; Yousaf, Nosheen (New York : Routledge, 2022)
This volume looks at the implications of transcultural humanities in South Asia. Drawing on contributors from around the globe, the entries look at literature and poetics, theory and praxis, borders and nations, politics, partition, gender and sexuality, the environment, representations in art, and pedagogy and the transcultural classroom.
Includes index.
Keywords: South Asian literature History and criticism; Humanities South Asia; Postcolonialism and the arts South Asia